KUALITAS JASA PELAYANAN DALAM UPAYA PENINGKATAN KEPUASAN KONSUMEN - Rainier Hendrik Sitaniapessy; Harry A.P. Sitaniapessy (Universitas Gunadarma, 2009)
Services are the key to hold the customer. In this era customer satisfaction must be focused. This article intended to explain how to manage and measure the service quality by marketing research. Every institution can improve their performance by employ service quality. There are five variables that can be use for measure the services quality. Keywords : service quality, costumer satisfaction, market research